2019
DOI: 10.1371/journal.pone.0221778
|View full text |Cite
|
Sign up to set email alerts
|

Examining inequalities in access to delivery by caesarean section in Nigeria

Abstract: Background Maternal deaths are far too common in Nigeria, and this is in part due to lack of access to lifesaving emergency obstetric care, especially among women in the poorest strata in Nigeria. Data on the extent of inequality in access to such lifesaving intervention could convince policymakers in developing an appropriate intervention. This study examines inequality in access to births by caesarean section in Nigeria. Methods Data for 20,468 women who gave birth in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…Women with private/employer insurance have higher probability to have CS compared to those with no insurance cover (aRRR = 1.6064). Moreover, studies have proved the positive relationship between wealth and CS deliveries [11,22,24], particularly elective CS [27]. In line with these studies, we also find that affluence, represented by the household wealth index, also has a positive influence the probability of CS delivery, both planned and unplanned.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Women with private/employer insurance have higher probability to have CS compared to those with no insurance cover (aRRR = 1.6064). Moreover, studies have proved the positive relationship between wealth and CS deliveries [11,22,24], particularly elective CS [27]. In line with these studies, we also find that affluence, represented by the household wealth index, also has a positive influence the probability of CS delivery, both planned and unplanned.…”
Section: Discussionsupporting
confidence: 89%
“…As for the potential explanatory variables, we selected them based on previous literature [11,[17][18][19][20][21][22][23][24][25][26][27]. We categorized them into several groups, namely spatial variables, maternal variables, demographic variables, access to information, and socio-economic variables.…”
Section: Variables Selectionmentioning
confidence: 99%
“…These factors have an improving effect on HRQoL, and this is supported by the study conducted in Sub-Saharan Africa. 35 …”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous studies [ 5 , 33 35 ], we found a disproportionately higher CS birth service uptake among richest/rich women as compared to poorest/poor women. Poor access to delivery by caesarean section remains mainly an issue among the economically and the socially deprived, which has serious implications for reducing maternal mortality and morbidity and perinatal and neonatal mortality and morbidity in the country [ 36 ]. Because of unaffordability of cost for CS service sometimes women are not able to deliver via CS (37) and hope for positive birth outcome even in case of prolonged labor since cost of CS is beyond their capability (38) as supported by previous studies that paying capability to CS service is one of the determinant for access to birth by CS [ 37 ].…”
Section: Discussionmentioning
confidence: 99%